THE EFFECT OF APPLICATION ERROR FREQUENCY AND DIGITAL SERVICE QUALITY ON CUSTOMER SATISFACTION WITH AT BANKS NTB SYARIAH - Veni Edriani; Ahadiah Agustina; Ahmad Hulaimi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of application error frequency and digital service quality on customer satisfaction with Islamic banking digital services, with an empirical study of Bank NTB Syariah in Indonesia. The study is based on increasing digitalization in Islamic banking services and the limited research integrating technological reliability and service quality within the Islamic banking context. The research methodology applies a quantitative approach with a survey technique involving 100 respondents who use the Bank NTB Syariah mobile banking application. Data analysis was conducted using multiple linear regression to evaluate the relationship between variables. The results show that digital service quality has a positive and significant effect on customer satisfaction (β = 0.536; p < 0.001), while application error frequency does not significantly affect customer satisfaction (β = 0.053; p = 0.548). The model explains 30.7% of the variance in customer satisfaction (R² = 0.307). These findings suggest that service speed, security, accessibility, and digital responsiveness are key factors shaping customer satisfaction perceptions. In conclusion, improving digital service quality is an essential strategy to enhance customer satisfaction, although improvements in system stability are still necessary. The implications of this research contribute to the development of more effective Islamic banking digital service strategies in Indonesia that are in line with Islamic principles.